2016
DOI: 10.1158/1535-7163.mct-15-0458
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Inhibitor of Topoisomerase I Is Selectively Toxic for a Subset of Non–Small Cell Lung Cancer Cell Lines

Abstract: SW044248, identified through a screen for chemicals that are selectively toxic for NSCLC cell lines, was found to rapidly inhibit macromolecular synthesis in sensitive, but not in insensitive cells. SW044248 killed approximately 15% of a panel of 74 NSCLC cell lines and was non-toxic to immortalized human bronchial cell lines. The acute transcriptional response to SW044248 in sensitive HCC4017 cells correlated significantly with inhibitors of topoisomerases and SW044248 inhibited topoisomerase 1 (Top1) but not… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Moreover, further studies in tumor spheroids demonstrated that the combination with seeMet 12 mediated significant spheroid size reductions compared to sorafenib alone (Figures 3D,E). These results are in line with a recent study in melanoma, where it was demonstrated that HGF/MET signaling contributed to resistance to the BRAF inhibitor vemurafenib via activation of ERK-MAPK and PI3K-AKT, and that pharmacologic inhibition of the cMet/AKT pathway restored the sensitivity (37). Consequently, dual targeting of cMet and BRAF in colorectal cancer may be a promising concept, and should be further explored, in particular since it may also offer hope to overcome resistance of several targeted drugs.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, further studies in tumor spheroids demonstrated that the combination with seeMet 12 mediated significant spheroid size reductions compared to sorafenib alone (Figures 3D,E). These results are in line with a recent study in melanoma, where it was demonstrated that HGF/MET signaling contributed to resistance to the BRAF inhibitor vemurafenib via activation of ERK-MAPK and PI3K-AKT, and that pharmacologic inhibition of the cMet/AKT pathway restored the sensitivity (37). Consequently, dual targeting of cMet and BRAF in colorectal cancer may be a promising concept, and should be further explored, in particular since it may also offer hope to overcome resistance of several targeted drugs.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the CPT-11 prodrug group (4-piperidinyl piperidine) causes AchE inhibition, which easily leads to acetylcholine syndrome, resulting in early severe diarrhea and other sideeffects (10). In order to overcome the above drawbacks of CPT-11, scientists have made several attempts to improve it (10,(17)(18)(19). In the present study, we designed and synthesized a novel 10-hydroxy CPT prodrug with a high efficiency and low toxicity (20,21).…”
Section: Antitumor Potential Of a Novel Camptothecin Derivative Zbh-mentioning
confidence: 99%
“…CPT-11 due to its low enzymatic conversion rate in vivo and its uncertain pharmacokinetic properties among individuals. In addition, the CPT-11 prodrug group (4-piperidinyl piperidine) causes AchE inhibition, which easily leads to acetylcholine syndrome, resulting in early severe diarrhea and other sideeffects (10). In order to overcome the above drawbacks of CPT-11, scientists have made several attempts to improve it (10,(17)(18)(19).…”
Section: Antitumor Potential Of a Novel Camptothecin Derivative Zbh-mentioning
confidence: 99%
See 1 more Smart Citation
“…This is why topo I inhibitors in clinical studies, such as camptothecin (CPT) and its derivatives topotecan, 10-hydroxy camptothecin (OPT), irinotecan (CPT-11), and rubitecan (9-NC), are normally toxic for rapidly growing tissues. Moreover, the cytotoxic essence of these drugs easily induces significant therapy-related secondary effects, including cardiotoxicity, myelosuppression, gastrointestinal toxicity, and even secondary leukemia . Hence, recent studies have concentrated on the exploitation of drugs or agents targeting topo II.…”
Section: Topo II Poisons and Catalytic Inhibitors/suppressorsmentioning
confidence: 99%